2016
DOI: 10.1155/2016/3569843
|View full text |Cite
|
Sign up to set email alerts
|

Patterning of Endothelial Cells and Mesenchymal Stem Cells by Laser-Assisted Bioprinting to Study Cell Migration

Abstract: Tissue engineering of large organs is currently limited by the lack of potent vascularization in vitro. Tissue-engineered bone grafts can be prevascularized in vitro using endothelial cells (ECs). The microvascular network architecture could be controlled by printing ECs following a specific pattern. Using laser-assisted bioprinting, we investigated the effect of distance between printed cell islets and the influence of coprinted mesenchymal cells on migration. When printed alone, ECs spread out evenly on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 33 publications
1
38
0
Order By: Relevance
“…4a ). During this time period, cells were proliferating (1 doubling per 2 days) and a progressive disorganization of patterns was observed similar to that in monoculture 32 . The MR images acquired with a short scan time (only 4 min) were nevertheless able to show the spread of the cells within the petri dish.…”
Section: Resultssupporting
confidence: 59%
“…4a ). During this time period, cells were proliferating (1 doubling per 2 days) and a progressive disorganization of patterns was observed similar to that in monoculture 32 . The MR images acquired with a short scan time (only 4 min) were nevertheless able to show the spread of the cells within the petri dish.…”
Section: Resultssupporting
confidence: 59%
“…This study indicated that EB diameter was affected by printing density, while there was no such a relevance between the diameter of printed colony and EB size (20). A similar study, in order to figure out the effect of MSCs and endothelial cells (ECs) co-culture on the migration potential, used a LBB system and showed that coprinting can reduce the ECs migration and results in initial pattern conservation (21).…”
Section: Inkjet Bioprintingmentioning
confidence: 87%
“…In addition, the crosstalk between human osseous cell sheets and HUVECs in the presence of laser assisted bioprinting biopapers leads to the formation of human prevascularized cell‐based osseous constructs that can be applied for autologous bone repair applications . However, when they were printed with MSCs, they remained in the printed lines, which again indicates the importance of coculture of the two cell types . In other attempts to enhance tissue survival and integration, vascularized heterogeneous tissue was developed by using ECs and fibroblasts ( Figure ).…”
Section: Bioprinted Bone Constructsmentioning
confidence: 99%